Low RCS and broadband metamaterial‐based low‐profile antenna using PCM. Issue 11 (25th May 2018) - Ren, Junyi; Jiang, Wen; Gong, Shuxi
Abstract : In this study, a novel cross layout of polarisation conversion metamaterial (PCM) is investigated for the first time. Based on the principle of phase cancellation, the cross structure can reduce radar cross section (RCS) significantly over a wider band compared with the chessboard configuration. The low‐profile metamaterial‐based antenna is composed of the cross PCM structure and a driven patch sandwiched between the PCM patches and the ground plane. Simulated and measured results show that compared with the microstrip patch antenna, the proposed antenna can achieve a wider impedance bandwidth of 6.05–7.52 GHz (21.7%) and milder gain variation in the working band, while the monostatic RCS can be reduced over 5.8–18.0 GHz (102.5%).